Rút gọn phân thức sau:
(10 - 2x)/(x2 - 10 + 25)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Câu 1:
a) 2x(3x+2) - 3x(2x+3) = 6x^2+4x - 6x^2-9x = -5x
b) \(\left(x+2\right)^3+\left(x-3\right)^2-x^2\left(x+5\right)\)
\(=x^3+6x^2+12x+8+x^2-6x+9-x^3-5x^2\)
\(=2x^2+6x+17\)
c) \(\left(3x^3-4x^2+6x\right)\div\left(3x\right)=x^2-\dfrac{4}{3}x+2\)
\(\dfrac{x^2-2x-8}{2x^2+9x+10}\)
\(=\dfrac{x^2-4x+2x-8}{2x^2+4x+5x+10}\)
\(=\dfrac{\left(x-4\right)\left(x+2\right)}{\left(x+2\right)\left(2x+5\right)}\)
\(=\dfrac{x-4}{2x+5}\)
\(\dfrac{x^2-2x-8}{2x^2+9x+10}\)
\(=\dfrac{\left(x-4\right)\left(x+2\right)}{2x^2+4x+5x+10}\)
\(=\dfrac{\left(x-4\right)\left(x+2\right)}{\left(x+2\right)\left(2x+5\right)}\)
\(=\dfrac{x-4}{2x+5}\)
1)10x-3x(x-5)+3(x2-4x)-3x
<=>3(x2-4x)+10x-3x-3x(x-5)
<=>3(x2-4x)=7x-3x(x-5)
<=>3x2-12x+7x-3x2+15x
<=>3x2-3x2-12x+7x+15x
<=>-12x+7x+15x
<=>10x
2)5y+1-4.5y
<=>51.5y-4.5y
<=>5y(51-4)
<=>5y.1
<=>5y
a) \(A=\left(x+2\right)\left(x^2-2x+4\right)-x^3+2\)
\(A=x^3+8-x^3+2\)
\(A=10\)
b) \(B=\left(x-1\right)\left(x^2+x+1\right)-\left(x+1\right)\left(x^2-x+1\right)\)
\(B=x^3-1-\left(x^3+1\right)\)
\(B=x^3-1-x^3-1\)
\(B=-2\)
c) \(C=\left(2x-y\right)\left(4x^2+2xy+y^2\right)+\left(y-3x\right)\left(y^2+3xy+9x^2\right)\)
\(C=\left(2x\right)^3-y^3+y^3-\left(3x\right)^3\)
\(C=8x^3-y^3+y^3-27x^3\)
\(C=-19x^3\)
a)
\(A=\left(x+2\right)\left(x-2\right)\left(x-2\right)-x^3+2\\ =\left(x^2-4\right)\left(x-2\right)-x^3+2\\ =x^3-2x^2-4x+8-x^3+2\\ =-2x^2-4x+10\)
b)
\(B=x^3-1-\left(x^3+1\right)\\ =x^3-1-x^3-1\\ =-2\)
c)
\(C=\left(2x\right)^3-y^3+\left(y\right)^3-\left(3x\right)^3\\ =8x^3-y^3+y^3-27x^3\\ =-19x^3\)
\(\Rightarrow\)\(A=\left(2x\right)^3-1-x^2\left(8x-1\right)\)
Thay \(x=10\) vào A ta đc:
\(A=\left(2\cdot10\right)^3-1-10^2\left(8\cdot10-1\right)=99\)